2013
DOI: 10.1099/vir.0.048249-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of antigenic sites of foot-and-mouth disease virus serotype Asia 1 and relationships with sites described in other serotypes

Abstract: Knowledge of the antigenic structure of foot-and-mouth disease virus (FMDV) has relevance in the development of diagnostic assays, in the evaluation of the antigenic variability and in the selection of appropriate vaccine strains. Antigenic sites have been investigated only in FMDVs of serotypes O, A and C, while it would be valuable to extend studies also to other serotypes. This paper reports the identification of antigenic sites involved in virus neutralization in the FMDV serotype Asia 1 by using a new pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 29 publications
1
49
0
Order By: Relevance
“…In the FMDV serotypes, both SAT1 and SAT2 are known to share one major antigenic region, the highly flexible VP1 G-H loop (Crowther et al 1993b), a cord of connected amino acid residues. Additional residues have also been identified on the SAT serotypes (Crowther et al 1993b;Grazioli et al 2006), as well as others on related serotypes A, O, C and Asia1 which may also occur within the SAT serotypes (Grazioli et al 2013;Kitson et al 1990;Lea et al 1994;Saiz et al 1991). For the H1N1 virus, experimental studies have identified four major antigenic sites (Caton et al 1982), as well as a number of other sites known to be important (McDonald et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the FMDV serotypes, both SAT1 and SAT2 are known to share one major antigenic region, the highly flexible VP1 G-H loop (Crowther et al 1993b), a cord of connected amino acid residues. Additional residues have also been identified on the SAT serotypes (Crowther et al 1993b;Grazioli et al 2006), as well as others on related serotypes A, O, C and Asia1 which may also occur within the SAT serotypes (Grazioli et al 2013;Kitson et al 1990;Lea et al 1994;Saiz et al 1991). For the H1N1 virus, experimental studies have identified four major antigenic sites (Caton et al 1982), as well as a number of other sites known to be important (McDonald et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The VP2 B-C loop is antigenic in all serotypes and contains the highly antigenic VP2 72 residue, which has been experimentally validated in all of the FMDV serotypes except SAT2 (Aktas and Samuel 2000;Crowther et al 1993a;Grazioli et al 2006Grazioli et al , 2013Kitson et al 1990;Lea et al 1994;Saiz et al 1991). The VP1 C-terminus has been proven to be antigenic in all but the Asia1 serotype, although it is almost certainly antigenic there also (Aktas and Samuel 2000;Baxt et al 1989;Grazioli et al 2006;Mateu 1995).…”
Section: Sat1 Datamentioning
confidence: 99%
See 3 more Smart Citations